548 The mediating role of recovery opportunities on future sickness absence from a gender- and age-sensitive perspective. (24th April 2018) - Boschman, JS; Noor, A; Sluiter, JK; Hagberg, M
Abstract : A lack of sufficient recovery during and after work may help to explain impaired health in the long run. We aimed to increase knowledge on the mediating role of recovery opportunities (RO) during and after work on future sickness absence from a gender- and age-sensitive perspective. We used data on RO from a Swedish national survey in 2011 and linked these to sickness absence (>14 days) two years later among the general working population (n=7, 649). Mediation of the relationship between gender and sickness absence by exposure to RO was studied through linear regression. We conducted separate analyses for RO during and after work and for three different age groups (16–29; 30–49; 50–64). The sample consisted of 3563 men and 4086 women. Sickness absence was higher among the women than among the men (11 days vs 5 days, p<0.001). Men reported statistically significantly more positive on their RO than women. RO during (ß 0.3–1.8) and after work (ß 0.4–0.6) mediated the relationship between gender and sickness absence. Mediation effects existed across age groups, with the strongest effects of RO during work found among the age group between 50 and 64 years of age (attenuation 36%). Our results indicate that gender inequality is also reflected in worse RO among women. This partially explains the increased risk of future sickness absence, particularly among those above 50 years of age. These findings show that RO during work deserve more attention in working life research.